Pengembangan Kualitas Kepribadian Guru - Oktradiksa, Ahwy (Nadwa, 2012)
Teachers play a role in improving the quality of education. As individuals, the teacher is the embodiment of all the unique characteristics according to its position as the teaching profession stakeholders. Personality is the primary foundation for self-realization as an effective teacher in carrying out their professional duties. This requires a teacher to be able to realize effective personal to carry out the functions and responsibilities. Teachers must know himself and is able to develop in the direction of the realization of a healthy personal and plenary. Teachers personality is an important factor for the success of ter-learning students. Personality of the teacher becomes an example for their students. Teachers personality into the factors that determine good or bad personality of the child. Good personality became a teacher requirements.